Application of P16, P63, cyclin D1 immunostaining and nuclear morphometric analysis for assessment of cervical dysplasia - Vukomanović Djurdjević, Biserka; Andrejić Višnjić, Bojana; Perić, Aleksandar; Nenadić, Dane; Baletić, Nenad (Vojnosanitetski pregled, 2022)
Background/Aim. Human papilloma virus (HPV) infection is the main etiological factor for the development of cervical precancerous dysplastic squamous intraepithelial lesions (SIL). The virus oncoproteins affect several proteins included in cell proliferation. The aim of this study was to evaluate application of immunohistochemical markers related to proteins of the cell cycle and, also, application of nuclear morphometric analysis for assessment of cervical dysplasia. Methods. Retrospective study included 78 women with detection of presence of high-risk HPV by polymerase chain reaction (PCR), with histopathology diagnosis low-grade SIL (LSIL) or high-grade SIL (HSIL). Immunohistochemical staining for p16, p63, cyclin D1 and morphometric analysis of the nuclear surface area were performed. The control group consisted of ten women without SIL and without HPV infection. This study was conducted in accordance with the Helsinki Declaration. Results. Comparing immunohistochemical expression of p16 and p63, highly statistically significant differences (p < 0.001) were established among the control, LSIL and HSIL groups, while cyclin D1 showed significant statistical difference (p < 0.05). Great variations were observed in nuclear morphology and nuclear surface area that had highly statistically significant differences (p < 0.001) among the control, LSIL and HSIL groups. Conclusion. This study demonstrated that immunohistochemical analysis of p16, p63 and cyclin D1 are important for diagnosis of dysplastic changes in cervical epithelium. Also, morphometric analysis of the nuclear surface area demonstrated a high significance for diagnosis of cervical dysplasia.